Pooled-Analysis of Association of Sievers Bicuspid Aortic Valve Morphology With New Permanent Pacemaker and Conduction Abnormalities After Transcatheter Aortic Valve Replacement - Zhang, Jiajun; Li, Xiaoxing; Xu, Feng; Chen, Yuguo; Li, Chuanbao (Frontiers in Cardiovascular Medicine, 2022)
Background: Studies on the association of Sievers bicuspid aortic valve (BAV) morphology with conduction disorders after transcatheter aortic valve replacement (TAVR) have not reached consensus. Methods: We here performed a pooled-analysis to explore whether Sievers type 1 BAV morphology increased risk of post-TAVR conduction abnormalities and permanent pacemaker implantation (PPI) compared to type 0. Systematic literature searches through EMBASE, Medline and Cochrane database were concluded on Dec 1st, 2021. The primary endpoint was post-TAVR new PPI and pooled as risk ratios (RRs) and 95% confidence intervals (CIs). Conduction abnormalities as the secondary endpoint were composite of post-TAVR PPI and/or new-onset high-degree atrial-ventricle node block and left-bundle branch block. Studies that reported incidence of outcomes of interest both in type 1 and type 0 BAV morphology who underwent TAVR for aortic stenosis were included. Results: Nine studies were finally included. Baseline characteristics were generally comparable, but type 1 population were older with higher surgical risk score compared to type 0 BAV morphology. In the pooled-analysis type 1 BAV had significantly higher risk of post-TAVR new-onset conduction abnormalities (RR=1.81, 95%CI 1.14-2.86, p= 0.011) and new PPI (RR = 1.97, 95%CI 1.29-2.99, p = 0.0016) compared to type 0. Random-effects univariate meta-regression indicated that no significant association between baseline characteristics and conduction abnormalities Conclusions: Sievers type 1 BAV morphology was associated with increased risk of post-TAVR PPI and conduction abnormalities compared to type 0. Dedicated cohort are warranted to further validate our hypothesis.